Comparative study of renal function test and thyroid hormone in chronic kidney disease - Nitesh Singhal; Dr. R.D. Mathur; Dr. Ajay Kumar Bhargava; Dr. Deepak Gupta (International Journal of Medical Research and Review, 2020)
Introduction: Biochemical parameters (urea, creatinine, uric acid, T3, T4, TSH) important in prognosis, monitoring of thyroid dysfunction, and chronic kidney disease. The present study was attempted to analyze these parameters in CKD patients and a healthy control group. Materials and methods: Fifty healthy control and 5o were chronic kidney disease subjects were taken serum urea, creatinine uric acid analyzed on the auto analyzer and T3, T4, TSH estimated on immunoassay analyzer. Ethical permission was taken from the institutional ethical committee. Results: Level of urea, creatinine, uric acid, and thyroid hormone T3, T4, TSH were found to be significant in the present study when compared with the control group. (Þ<0.0001). Conclusion: It was observed that levels of urea, creatinine, uric acid, and T3, T4, TSH deranged value found in chronic kidney disease subjects.